Prediction of corrosion resistance of the casing bottom structure caused by H₂S-CO₂ affect in highly mineralized formation fluids of iraq oil deposits - Donskyi, D. F.; Nesterenko, S. V.; Neamah, Ameer; Tulska, Alona Gennadiivna; Dihtenko, K. M. (VÚRUP, 2022)
The main reason of corrosion destruction of casing surface has been considered. Based on gravimetric, potentiometric and optical studies using mathematical planning of the experiment, the influence of various factors on the corrosion rate has been studied. Model of regression for different types of steel are compared and the role of inhibition in this process has been analyzed.
Keywords: сorrosion; сorrosion rate; hydrogen sulfide; carbon monoxide; casing; regression